Nanobody binding to a conserved epitope promotes norovirus particle disassembly - Koromyslova, Anna D.; Hansman, Grant S. (Journal of virology, 2015)
Human noroviruses are icosahedral single-stranded RNA viruses. The capsid protein is divided into shell (S) and protruding (P) domains, which are connected by a flexible hinge region. There are numerous genetically and antigenically distinct noroviruses, and the dominant strains evolve every other year. Vaccine and antiviral development is hampered by the difficulties in growing human norovirus in cell culture and the continually evolving strains. Here, we show the X-ray crystal structures of human norovirus P domains in complex with two different nanobodies.
Accepted manuscript posted online 17 December 2014
Gesehen am 22.07.2020